Pengaruh Model Pembelajaran dan Minat Siswa Terhadap Hasil Belajar Matematika - Binti Khusnul Chotimah (Universitas Serang Raya, 2018)
Influence Model of learning and Learning Interest Against the results of the Learning of Mathematics (Model of learning, the learning interest of mathematics learning outcomes, ANOVA two lanes and experimentation. The goal of penelitihan is to know the influence of learning against the results of learning math student SMK negeri in Pandeglang, the influence of the interest in the results of learning math student SMK negeri in Pandeglang, influence the learning interaction student learning and interest against the results of learning math student SMK negeri in Pandeglang. The results of penelitihan showed there are influences of yan siqnifikan learning against the results of learning math students of SMK negeri in Pandeglang model learning and learning interest of students towards learning outcomes for Mathematics (high and low)